2021
DOI: 10.31025/2611-4135/2021.15144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Injuries Among Waste Pickers. A Case Study in Nigeria

Abstract: Waste picking might provide, in low-income countries, a livelihood for many individuals representing an important survival strategy. However, during their activities, waste pickers are at risk of encountering harmful waste, which could cause injuries and other infectious diseases. This paper investigates the occurrences of injury among waste pickers and the methods they use to treat the injuries in Bauchi city, Northeastern Nigeria. A total of 322 waste pickers were randomly selected across 80 waste pickers’ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
1
8
1
1
Order By: Relevance
“…The percentages of scavengers that attained primary, secondary and tertiary educations were 11.9%, 34.8% and 10.3% respectively. Similar study in Bauchi reported none of the waste scavengers interviewed attended beyond secondary education (Ali and Yusuf, 2021). This findings contrast with the present study that reported 10.3% of the respondents attained beyond secondary Education.…”
Section: Results and Discussion 41 Socio Demographic Characteristics ...contrasting
confidence: 99%
See 2 more Smart Citations
“…The percentages of scavengers that attained primary, secondary and tertiary educations were 11.9%, 34.8% and 10.3% respectively. Similar study in Bauchi reported none of the waste scavengers interviewed attended beyond secondary education (Ali and Yusuf, 2021). This findings contrast with the present study that reported 10.3% of the respondents attained beyond secondary Education.…”
Section: Results and Discussion 41 Socio Demographic Characteristics ...contrasting
confidence: 99%
“…The major reason (90%) that attracted the people into scavenging is due to income and employment it provides to them as a result of poverty. Overall joblessness and economic considerations as found in this study dominated the discussions in other studies as to why they engage in the activity ( (Nzeadibe, 2009;Lambu, 2016;Adama 2014;Dankani, 2010;Ali and Yusuf, 2021).Scavengers revealed loss of hope and disappointment as result of the difficulty in securing job in the formal sector make them struggle and sift through the mountain of refuse for sustenance. From all indications, most of the scavengers are in the occupation not by choice, but due to increased levels of unemployment and poverty.…”
Section: Reasons For Engaging In Waste Scavengingsupporting
confidence: 56%
See 1 more Smart Citation
“…Skin lesions, diarrheal disease, eye discharge and bodily wounds were each seen in under 5% of the sample. 48 Work-Related Injury Ali et al (2021), in a 2019 study set in Bauchi city, Bauchi State, consider workplace injury among people employed in waste-picking, which "involves the collection, purchase, and recovery of materials for economic bene t" from waste and refuse dumps. Here, authors identify that, of their 313 participants, most were "Internally Displaced Persons (IDPs) and Almajiri children", but do not disaggregate their ndings by participant type.…”
Section: Resultsmentioning
confidence: 99%
“…Many were unable to afford the school fees and uniforms because of the financial hardships they faced. A quantitative study reported that 35% of Nigeria's dumpsite waste pickers had no formal education, while 41% had attended primary school and 24% had attended secondary school [45].…”
Section: Educationmentioning
confidence: 99%